1999
DOI: 10.1086/308017
|View full text |Cite
|
Sign up to set email alerts
|

Central Masses and Broad‐Line Region Sizes of Active Galactic Nuclei. I. Comparing the Photoionization and Reverberation Techniques

Abstract: The masses and emission-line region sizes of AGNs can be measured by "reverberation-mapping" techniques and we use these results to calibrate similar determinations made by photoionization models of the AGN line-emitting regions. Reverberation mapping uses the light travel-time delayed emission-line response to continuum variations to determine the size and kinematics of the emission-line region. We compile a sample of 17 Seyfert 1 galaxies and 2 quasars with reliable reverberation and spectroscopy data, twice… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
817
5
1

Year Published

2001
2001
2006
2006

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 651 publications
(870 citation statements)
references
References 50 publications
47
817
5
1
Order By: Relevance
“…We find that IC 4329A is an outlier in all the relations discussed in Wandel, Peterson & Malkan 1999 as well as in Peterson et al 2000. This leads us to suspect the virial BH mass of this object.…”
Section: Determination Of Bulge Massmentioning
confidence: 68%
See 1 more Smart Citation
“…We find that IC 4329A is an outlier in all the relations discussed in Wandel, Peterson & Malkan 1999 as well as in Peterson et al 2000. This leads us to suspect the virial BH mass of this object.…”
Section: Determination Of Bulge Massmentioning
confidence: 68%
“…For NAB 0205+024, PG 1402+261 and PG 1444+407 we take the host galaxy absolute mag-2 The virial mass for IC 4329A is adopted from Wandel 1999 who has adopted it from Wandel, Peterson & Malkan 1999. We find that IC 4329A is an outlier in all the relations discussed in Wandel, Peterson & Malkan 1999 as well as in Peterson et al 2000.…”
Section: Determination Of Bulge Massmentioning
confidence: 99%
“…One important application for such measurements is as a consistency check on the black hole masses determined from reverberation mapping of nearby Seyfert 1 galaxies (Wandel, Peterson, & Malkan 1999;Kaspi et al 2000). Gebhardt et al (2000b) and Ferrarese et al (2001) have shown that the reverberation masses of Seyfert 1 galaxies are in good agreement with the M −σ relation of nearby galaxies; this is a reassuring sign that the reverberation measurements give reasonable estimates of the black hole masses.…”
Section: Can the Stellar Velocity Dispersions Of Quasar Host Galaxiesmentioning
confidence: 94%
“…Consequently, BH masses in local AGN are commonly mapped with alternative techniques such as reverberation mapping (Blandford & Mc Kee 1982;Peterson 1993; see Peterson these proceedings) where one estimates the virial mass inside the broad-line region (BLR) by combining the velocity of the BLR with an estimate of the size of the BLR based on time delay measurements. Reverberation mapping can typically probe scales ∼ 600 R s−bh and has yielded BH masses for several tens of AGN (Peterson 1993; Wandel, Peterson, & Malkan 1999;Kaspi 2000). Earlier controversies existed on the reliability of the method due to purported systematic differences in the BH-to-bulge mass ratio between AGN with reverberation mapping data and quiescent galaxies or QSOs.…”
Section: Measurement Of Bh Massesmentioning
confidence: 99%